2005
DOI: 10.1136/jmg.2004.028738
|View full text |Cite
|
Sign up to set email alerts
|

Extensive scanning of the calpain-3 gene broadens the spectrum of LGMD2A phenotypes

Abstract: Background: The limb girdle muscular dystrophies (LGMD) are a heterogeneous group of Mendelian disorders highlighted by weakness of the pelvic and shoulder girdle muscles. Seventeen autosomal loci have been so far identified and genetic tests are mandatory to distinguish among the forms. Mutations at the calpain 3 locus (CAPN3) cause LGMD type 2A. Objective: To obtain unbiased information on the consequences of CAPN3 mutations. Patients: 530 subjects with different grades of symptoms and 300 controls. Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
68
2
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(76 citation statements)
references
References 47 publications
5
68
2
1
Order By: Relevance
“…Interestingly, previous reports had indicated an early onset in men rather than in women, difference relative to wheelchair dependent patients between genders or a more rapid progression in men 23, 31, 32. Interestingly, a difference in fiber atrophy between genders has recently been reported in LGMD,33 a fact which may support of this dissimilarity.…”
Section: Discussionmentioning
confidence: 86%
“…Interestingly, previous reports had indicated an early onset in men rather than in women, difference relative to wheelchair dependent patients between genders or a more rapid progression in men 23, 31, 32. Interestingly, a difference in fiber atrophy between genders has recently been reported in LGMD,33 a fact which may support of this dissimilarity.…”
Section: Discussionmentioning
confidence: 86%
“…23 -26 The onset of muscle weakness and the progress of clinical course may vary considerably, as may the spectrum of phenotypes that is becoming increasingly wider, including, hyperCKemia, pseudometabolic myopathy and eosinophilic myositis. 5,27,28 Genotype -phenotype correlation studies have demonstrated that this clinical variability may be only partly attributable to gene mutations 24,26,29,30 (interfamilial and intrafamilial variability because of the same mutation), which suggests that additional epigenetic/environmental factors might play a role in modulating the phenotype expression. The molecular diagnosis of LGMD2A is increasingly being demanded because of the high frequency of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…These transcripts are variably expressed and not always detectable in the mutant patients. 15,18,36 In our study, it seems reasonable to deduce that the observed variability between two siblings sharing the same mutation is owing to the ability to splice the mutant allele. The clinical heterogeneity observed in this family supported findings of previous studies concerning CAPN3-splicing mutations (Table 1).…”
Section: Intronic Alterations Affect Splicing Of Capn3 Genementioning
confidence: 96%